2019
DOI: 10.21873/invivo.11493
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Somatic Mutations in Colorectal Cancer With Peritoneal Metastasis

Abstract: Background: To analyze for genetic mutations which may presage peritoneal metastasis by using targeted next-generation sequencing (NGS). Materials and Methods: Formalin-fixed, paraffin-embedded primary tumor specimens were obtained from 10 patients with small obstructing colorectal cancer and peritoneal metastasis (group A) and five with large non-obstructing colorectal cancer and no recurrence (group B). DNA was extracted for the sequencing of 409 cancer genes. The distribution of genetic mutations was compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The implantation of tumor cells in the abdominal cavity can be caused by the flow of blood and lymph into the abdominal cavity by the severed blood vessels and lymphangioma embolus, the pulling and squeezing of tumor tissues during the operation, or the inflow of tumor cells through the intestinal stump with intestinal fluid. Patients with peritoneal metastasis had a worse prognosis than those without, and the higher the degree of peritoneal metastasis, the shorter the survival time [ 34 , 35 ]. The addition of simvastatin is not a factor affecting the mean survival time of CRC patients, but it can prolong the overall survival time of patients within 3–5 years, and it is expected to be used as a routine drug regimen to optimize the prognosis of CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The implantation of tumor cells in the abdominal cavity can be caused by the flow of blood and lymph into the abdominal cavity by the severed blood vessels and lymphangioma embolus, the pulling and squeezing of tumor tissues during the operation, or the inflow of tumor cells through the intestinal stump with intestinal fluid. Patients with peritoneal metastasis had a worse prognosis than those without, and the higher the degree of peritoneal metastasis, the shorter the survival time [ 34 , 35 ]. The addition of simvastatin is not a factor affecting the mean survival time of CRC patients, but it can prolong the overall survival time of patients within 3–5 years, and it is expected to be used as a routine drug regimen to optimize the prognosis of CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mediators of Inflammation database and firstly proposed as an independent prognostic factor (Table S14). PAX5 was identified to be relevant to CRC with peritoneal metastasis [77].…”
mentioning
confidence: 99%
“…Subsequently, mechanistic investigation showed that LINC00586 knockdown upregulated ASXL1 expression, whereas ectopic expression of LINC00586 downregulated ASXL1 expression in CRC cells. Aberrantly expressed ASXL1 has also been identified in CRC previously ( Lee et al, 2019 ). However, we were the first reporting the regulatory relationship between LINC00586 and ASXL1.…”
Section: Discussionmentioning
confidence: 87%